ANALISIS TRANSPARANSI PARTISIPASI DAN AKUNTANBILITAS PENGELOLAAN DANA DESA (Studi Kasus pada Desa Sako Kecamatan Pangean Kabupaten Kuantan Singingi Provinsi Riau Tahun Anggaran 2018) - Yoga Alwindria; Taufeni Taufik; Nur Azlina (INDONESIAN JOURNAL OF ACCOUNTING AND GOVERNANCE, 2019)
This study aims to analyze the management of the Village Fund in Sako Village. It alsoanalyzes the mechanism of transparency, participation and accountability in the management of the Sako Village Fund. Last, itanalyzes the guidance and supervision procedures for managing the Sako Village Fund.This type of research is a qualitative study and uses a comparative descriptive approach. In this research, the researcher describes Transparency, Participation and Accountability of Sako Village financial management which includes planning, implementation, administration, reporting, accountability, guidance and supervision of village financial management and comparative compliance with Law Number 6 of 2014 and Permendagri Number 20 of 2018 .The results showed that in general the management of village funds in Sako Village from the planning, implementation, administration, reporting, and accountability stages can be said to be Transparent, Participatory, and Accountable. Although at each stage there are still small notes that become homework for the village government to be improved for the better. The training carried out by the Riau Provincial Government and Kuantan Singingi Regency can be said to be very good.